Sales Promotion Tactics in Retailing: Fair vs Unfair - Singla, Babita; Sharma, Sandhir ,; Singh, Amandeep (International Journal of Psychosocial Rehabilitation, 2020)
Today’s customer evaluates the pros and cons of every offering / scheme available in the market before making the final purchase decision. But still there are various offerings which create confusion in the kinds of the customer / channel partner and they are duped by the same. Some of these offerings are meant to increase the sales of the end product directly. In the designs of the posters, the word up to is shown in such a small size that it creates illusion in the mind of the end customer. They are attracted towards the store and when they visit there, they are forced to buy even some of the unplanned products thus earning huge benefits for the retailers. And some of the customers return empty handed because the offers are not meant for the products in which they are interested in. Ethics is one of the most important aspect of behavior and social sciences dealing with what is right and what is wrong. This paper discusses the concept that how the facts are twisted in the advertisements and promotions. What is the effect of this untruthful advertising on the customers / visitors and various laws related to these behavior of marketers